Owning a pet rabbit - Glover, David, 1953 Sept. 4-; Glover, Penny (North Mankato, Minn. : Sea to Sea, 2008)
Provides guidance for choosing and caring for a pet rabbit, covering different breeds, hutches and cages, food, health care, and other aspects.
Includes bibliographical references (p. 31) and index.
5.7
3-6
Keywords: Rabbits -- Juvenile literature; Rabbits; Rabbits; Rabbits; Pets